(untitled) (Archive of Conferences, 2022)
The article considers the increase in the reliability of the gas turbine operation in the variable climatic conditions of Uzbekistan, by controlling the air quality at the inlet of the gas turbine compressor in order to bring its parameters closer to the calculated ones.